(3GdWHQj GdeDQN hGdcJGHI GdJGQjNjI aj GdYUQ GdYHGSj (B/s - (3cGJHj, ZjOGA YGOd NRfIs ((3HjQhJ (B- (3dHfGf (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ,s (3YeGf (B- (3GdCQOf (B:s (3OGQ GdaGQS ddfTQ hGdJhRjY ,s, 2017)
(3JYO efgLjI GdcJGHI GdJGQjNjI ef Cge ehVhYGJ GdHMK GdJGQjNj, HEYJHGQgG eaJGM gPG GdYde hGdefWb GdPj jSjQ Ydjg GdHGMKjf aj EYOGOge ddHMhK hGdOQGSGJ GdLGOI, hdcj JSJbje YedjI GdQUO GdJGQjNj ddQhGjGJ GdhGQOI YfO eDQNjfG GdChGFd aj GdbQhf GdgLQjI GdChdi, dG HO ef age LejY MjKjGJ GdefgL GdeJHY YfO cd eDQN, ef NdGd GdJYQa Ydi OhQg, hCSdhHg aj YQV GdeGOI GdJGQjNjI, hdeG cGf GdWHQj ehShYI JGQjNjI KQjI jfHZj OQGSJgG hJMdjd CWQgG heVGejf CNHGQgG, JWdH EHJOGA GdJYQa Ydi efgLg hJObjb CSdhHg GdeJHY aj EYOGOgG, NGUI Cf OQGSJg ceDQN, HTcd efaQO, jYO XGgQI JGQjNjI dgG CHYGOgG hejRGJgG, aGdEeYGf ajg gh aj GdMbjbI bQGAI eJCfjI deQMdI egeI ef JGQjN GdMVGQI GdESdGejI, dPdc GLJgOJ GdOQGSI aj Gdhbha YfO LejY MjKjGJ efgLg ShGA eUGOQ QhGjGJg Ch GdESfGO Ch GdfbO Ch GdJCQjN dOjg(B.s
(3jTJed Ydi edGMb(B.s
(3HHdjhLQGajI (B: (3UaMI (B373-407.s
Keywords: (3GHf LQjQ GdWHQj, eMeO Hf LQjQ Hf jRjO,s -- 224-310 (3gLQjs -- (3eSGgeGJ aj GdJCQjNs; (3JQGLe s -- (3QLGd ef GdJGQjNs -- (3GdeDQNjfs -- (3GdHMhK GdJGQjNjIs -- (3JGQjNs -- (3GdYUQ GdYHGSj s